Parturition and the perinatal period: can mode of delivery impact on the future health of the neonate?. (15th April 2018) - Tribe, R. M.; Taylor, P. D.; Kelly, N. M.; Rees, D.; Sandall, J.; Kennedy, H. P.
Abstract: Caesarean section and instrumental delivery rates are increasing in many parts of the world for a range of cultural and medical reasons, with limited consideration as to how 'mode of delivery' may impact on childhood and long‐term health. However, babies born particularly by pre‐labour caesarean section appear to have a subtly different physiology from those born by normal vaginal delivery, with both acute and chronic complications such as respiratory and cardio‐metabolic morbidities being apparent. It has been hypothesized that inherent mechanisms within the process of labour and vaginal delivery, far from being a passive mechanical process by which the fetus and placenta are expelled from the birth canal, may trigger certain protective developmental processes permissive for normal immunological and physiological development of the fetus postnatally. Traditionally the primary candidate mechanism has been the hormonal surges or stress response associated with labour and vaginal delivery, but there is increasing awareness that transfer of the maternal microbiome to the infant during parturition. Transgenerational transmission of disease traits through epigenetics are also likely to be important. Interventions such as probiotics, neonatal gut seeding and different approaches to clinical care have potential to influence parturition physiology and improve outcomes for infants. Abstract :  The different experiences of babies born vaginally and by caesarean section impacts several developmental and physiological processes that in turn influence short‐ and long‐term health.